Bone Specific Alkaline Phosphatase and Serum Calcification Propensity Are Not Influenced by Etelcalcetide vs. Alfacalcidol Treatment, and Only Bone Specific Alkaline Phosphatase Is Correlated With Fibroblast Growth Factor 23: Sub-Analysis Results of the ETACAR-HD Study - Dörr, Katharina; Hödlmoser, Sebastian; Kammer, Michael; Reindl-Schwaighofer, Roman; Lorenz, Matthias; Reiskopf, Bianca; Jagoditsch, Rahel; Marculescu, Rodrig; Oberbauer, Rainer (Frontiers in Medicine, 2022)
Secondary hyperparathyroidism in chronic kidney disease poses a major risk factor for vascular calcification and high bone turnover, leading to mineralization defects. The aim was to analyze the effect of active vitamin D and calcimimetic treatment on fibroblast growth factor 23 (FGF23), serum calcification propensity (T50), a surrogate marker of calcification stress and bone specific alkaline phosphatase (BAP) in hemodialysis. This is a subanalysis of a randomized trial comparing etelcalcetide vs. alfacalcidol in 62 hemodialysis patients for 1 year. We compared the change of BAP and serum calcification propensity between the two medications and assessed the influence of FGF23 change over time. We found no significant differences in the change of BAP or serum calcification propensity (T50) levels from baseline to study end between treatment arms (difference in change of marker between treatment with etelcalcetide vs. alfacalcidol: BAP : 2.0 ng/ml [95% CI-1.5,5.4], p = 0.3; T50: –15 min [95% CI –49,19], p = 0.4). Using FGF23 change over time, we could show that BAP levels at study end were associated with FGF23 change (–0.14 [95% CI –0.21, –0.08], p < 0.001). We did not observe the same association between FGF23 change and T50 (effect of FGF23 change on T50: 3.7 [95% CI –5.1, 12], p = 0.4; R2 = 0.07 vs. R2 = 0.06). No significant difference was found in serum calcification propensity (T50) values between treatment arms. FGF23 was not associated with serum calcification propensity (T50), but was negatively correlated with BAP underlying its role in the bone metabolism. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT03182699].